A Marine-based Meriolin (3-Pyrimidinylazaindole) Derivative (4ab) Targets PI3K/AKT /mTOR Pathway Inducing Cell Cycle Arrest and Apoptosis in Molt-4 Cells - Chashoo, Gousia; Singh, Umed; Singh, Parvinder P.; Mondhe, Dilip M.; Vishwakarma, Ram A. (Clinical Cancer Drugs, 2019)
Background: Cyclin-dependent kinases play a central role in the control of cell division and therefore it is not surprising that cancer exhibits some features that disturb the normal controls over the cell cycle. Previous studies related to the development of 3-Pyrimidinylazaindole (Meriolin) derivatives as novel Cyclin dependent kinase inhibitors highlighted 4ab as the most potent inhibitor. Objective: The main objective of the current study was to understand the mode of cell death and the effect of 4ab on major cellular networking pathways in cancer. Methods: Preliminary apoptotic studies were carried out using flowcytometer and electron microscope. The effect on cellular signalling was studied via western blotting. Results: 4ab was found to inhibit the enzymatic activity of CDK2. The inhibition of CDK2 activity was found to be associated with the down-regulation of P-cdc-25 and arrest of cells in G0-G1 phase of the cell cycle in lymphoblastic leukemia cells. Further, 4ab was found to affect AKT-mToR pathway by down-regulating the expression of major proteins including P-m-TOR (2448), P110α, P-AKT (S473) and P-p-70S6K. Conclusion: Current study shows that the potent anticancer potential of 4ab is mediated via cellular apoptosis, dysregulation of mitochondrial membrane potential and arrest of G1 phase in Molt-4 cells. Further, target-based studies showed the effect of 4ab on one of the major cellular signalling pathways deregulated in cancer.
Keywords: apoptosis